Psychosocial well-being among individuals with chronic kidney disease undergoing hemodialysis treatment and their caregivers: a protocol of a mixed method study in Sri Lanka and Poland - Bulathwatta, Darshika Thejani; Borchet, Judyta; Rudnik, Agata; Bidzan, Mariola (Frontiers in Psychology, 2023)
Chronic Kidney Disease (CKD) can be identified as one of the non-communicable diseases (NCDs) which affect millions of people worldwide, including in Sri Lanka and Poland. The prevalence of CKD has been rising over the last three decades due to the identification of CKD with unknown etiology and the increment of NCDs such as hypertension and diabetes mellitus among the Sri Lankan population. Poland can be identified as a European country that has 4 million patients with CKD, which is the second most common chronic disease in the country.CKD is associated with the physical, economic, psychological, and social burden on patients and their caregivers. The current study is aimed to investigate the psychosocial well-being of CKD patients and their caregivers in Sri Lanka and Poland.The current study is a mixed-method study aimed to investigate the psychosocial well-being of individuals with chronic kidney disease undergoing hemodialysis and their caregivers in Sri Lanka and Poland. Participants in the quantitative part of the project will be individuals with chronic kidney disease undergoing hemodialysis from Sri Lanka (n=63) and Poland (n=63) who are currently undergoing hemodialysis treatment. Kidney Disease Quality of Life-Sort Form, Beck Depression Scale, Test of Self-Conscious Affect, The Courtauld Emotional Control Scale, Acceptance of Illness Scale, and a demographic and medical information sheet will be used in both Sri Lankan and Polish samples. Apart from that, the qualitative phase of Formatted: Superscript